Revisiting the right to remain silent in Malaysia: its significance to the accused in criminal trials - Zulazhar Tahir,; Jal Zabdi Mohd Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2024)
When a person faces trial in Malaysia, he has the right to refuse to testify and cannot be forced to do so, known as the right to remain silent. This right protects individuals from self-incrimination. In Malaysia, the right to remain silent is enshrined in the Federal Constitution. However, following the 2006 amendment of the Criminal Procedure Code, the right of the accused to remain silent during trial may not necessarily be advantageous. An analytical approach is adopted throughout the analysis of this issue. This article looks into this amendment which states that when a prima facie case is established against the accused and the prosecution presents credible evidence substantiating each element of the offense, this would justify a conviction if the evidence goes unrebutted or unexplained. It follows that under such scenario, the accused right to remain silent now no longer protects him anymore, rather such right to remain silent exposes himself to a risk of a conviction. Hence this article delves into the current ensuing problem of the increased risk of conviction should the accused choose to remain silent when the prosecution is able to prove prima facie case against him via presentation of credible proof which prove all elements of crime. The article eventually suggests that in overcoming such predicament, the right of the accused to remain silent under such circumstance should be eliminated to ensure that the right to a fair trial is accorded to the accused at all times during trial.